Access to the Utilization of Triple Elimination Disease Screening Services for Pregnant Women in Rural Areas: A Lesson from Kintamani-Bali District - Ni Ketut, Andayani; Seri Ani, LUH; Dinar Saurmauli, Lubis (YCAB Publisher, 2025)
Background: Kintamani District is a rural area in Bangli-Bali Regency the scope of the program to prevent the transmission of HIV, Syphilis and Hepatitis B (triple elimination) from mother to child has not reached the target. Accessibility factors can affect the implementation of triple elimination screening in pregnant women. Objective: This study aims to analyze the access factors to the utilization of triple elimination screening services. Methods: A cross-sectional study was conducted on pregnant women in the Kintamani District area of Bali. A total of 169 pregnant women were involved in this study, selected by the multistage random sampling method. Pregnant women who live in the Kintamani sub-district, are pregnant with gestational age in the third trimester and are willing to participate as a sample. Meanwhile, the exclusion criteria are set if the pregnant woman is sick when the data collection is carried out. Data on the utilization of triple elimination screening services and accessibility aspects were collected by interview method using questionnaires. The data from the research results were analyzed univariate, multivariate, and multivariate. The logistic regression test was carried out to determine the relationship between the access factor and the utilization of triple elimination services. Results: 33.7% of pregnant women used triple elimination screening services. Pregnant women who used triple elimination screening services were more common in mothers aged 20-35 years (65.4%), parity ≤2 (68.9%), higher education level (78.9%), working status (64.9%), high economic status (73.9%), distance from home to service places close (78.8%), good availability of Triple Elimination screening tools and materials (92.7%), The affordability of the cost of the Triple Elimination screening service is good (78.1%), the suitability of the implementation of the Triple Elimination screening service is good (66.7%). Factors related to the use of triple elimination screening services are the distance between the home and the service place (aOR=5.4; 95%CI=2.3-17.1; p=0.000), the availability of good screening equipment and materials (aOR=22.2; 95%CI=5.0-98.4; p=0.000), the affordability of the cost of good triple elimination screening services (aOR=14.5; 95%CI= 3.6-57.9; p=0.000), and the suitability of the implementation of good triple elimination screening services (aOR=6.3; 95%CI= 1.3-29.9; p=0.020). Conclusion: The use of triple elimination screening services is related to the distance of the home, the availability of tools and materials, the affordability of service costs, and the suitability of service implementation. This research contributes to an increasing understanding of the relationship between access factors and the use of triple elimination services for pregnant women. To increase the coverage of triple-elimination services, this study suggests maximizing the role of health workers in promoting the importance of triple-elimination screening and providing services following the triple-elimination screening procedure for pregnant women.